A Systematic Review of Tablet Technology in Mathematics Education - Svela, Alexander; Nouri, Jalal; Viberg, Olga; Zhang, Lechen (International Journal of Interactive Mobile Technologies (iJIM), 2019)
In 2019, the mobile learning body of knowledge is extensive and much is known about the technology impacts and affordances of mobile devices in educational settings. A particular focus has now shifted toward specific technologies in specific subjects. Mathematics is one such subject and tablets are one such technology that is gaining attention. This systematic review representing the latest generation of tablet technology within the tablet-mediated learning in mathematics body of knowledge sought to derive evidence that supported questions into (a) what math sub-disciplines were covered, (b) what technology (application/hardware) was utilized, and (c) what pedagogical approaches were deployed in educational settings. This included analysis of the (d) advantages and (e) disadvantages present in those elements. Thirty-nine relevant articles were collected from various academic technology and educational databases. The results demonstrate that tablets are being predominantly deployed in various sub-disciplines such as Arithmetic, Computation, and Geometry with the iPad as the dominant choice for tablet hardware/applications. Pedagogical approaches lean heavily on game-based learning, environment interaction, and special needs support. Technological advantages include increased collaboration and mathematics engagement enabled by tablet mobility and a high potential for customization of solutions. Developers, teachers, and researchers need to be informed of potential challenges in designing content for tablet technology deployments in mathematics.